Effect of Nisin on the Quality Characteristics of Fiber-Enriched Chicken Harrisa - Kumar, Lokesh; Bhat , Z.F.; Kumar, Sunil (Journal of Meat Science, 2016)
Fiber-enriched chicken Harrisa was developed by incorporating optimum level of different fiber sources viz. oat bran (10%), wheat bran (10%) and barley bran (5%) separately. The products developed were further treated with nisin (500 I.U/g) and were aerobically packaged in low density polyethylene pouches along with control and assessed for oxidative stability and storage quality under refrigerated (4±1oC) conditions. The products were evaluated for various physicochemical, microbiological and sensory parameters at regular intervals of 0, 7, 14 and 21 days. The products incorporated with nisin showed significantly (p<0.05) lower values for total plate count and psychrophilic count throughout the period of storage. Coliforms were not detected throughout the period of storage. Significantly (p<0.05) higher scores were observed for various sensory parameters of the products incorporated with nisin. Nisin successfully improved the storage quality of the fiber-enriched chicken Harrisa during refrigerated (4±1oC) storage and may be commercially exploited to improve the storage quality of the product.